LANDSLIDE AREA MAPPING IN DAMPIT SUBDISTRICT, MALANG DISTRICT, EAST JAVA PROVINCE USING SATELLITE IMAGERY OF GRAVITY DATA FOR DISASTER MITIGATION - Sutasoma, Muwardi; Susilo, Adi; Maryanto, Sukir; Aprilia, Faridha; Bunga Puspita, Mayang; Habibiy Idmi, Mohammad; Hasan, Muhammad Fathur Rouf; Almais, Agung Teguh Wibowo; Herwiningsih, Sri (Universitas Mataram, 2025)
Research using satellite imagery of gravity data has been conducted in the Dampit District, Malang Regency, East Java Province. This research was conducted to identify areas vulnerable to landslides. The results of this research can serve as a basis for the government to develop effective landslide disaster mitigation policies, thereby minimizing the losses incurred. The data used is TOPEX satellite gravity data in the form of Free Air Correction data, and supported by landslide vulnerable areas data from the InaRisk satellite. The research area is 23 km x 16 km with 2 km spacing between points and 184 measurement points. Furthermore, the research area is divided into four areas: Area A1, Area A2, Area A3, and Area A4.Â The residual anomaly value in the study area is between 82.7 mGal to 142.4 mGal. The residual anomalies are more variable due to the local nature of the anomalies. The correlation between the residual anomaly value and InaRisk satellite image data shows that Area A4 is the most vulnerable to landslides, especially if there is a trigger such as an earthquake.Â This is because Area A4 has a low-density value, a large fault, and is the contact area between the Mandalika Formation and Wuni Formation.